New records of the snow bass Serranus chionaraia (Perciformes: Serranidae) confirm an established population in the Brazilian Province - Pimentel, Caio R.; Vilar, Ciro C.; Rolim, Fernanda A. [UNESP]; Abieri, Maria L.; Joyeux, Jean-Christophe (Wiley-Blackwell, 2019)
The snow bass Serranus chionaraia is a small-bodied reef fish presumed to be restricted to the Caribbean Province, with a single specimen captured south of the Amazon River mouth. Recent surveys with baited remote underwater stereo-video systems detected the species c. 1900 km southward. Meristic and morphometric characters of two specimens examined in this study confirmed the species identity, which greatly extends the species' range southward on the eastern coast of Brazil and indicates the presence of an established population of S. chionaraia in the Brazilian Province.
Keywords: Abrolhos Bank; BRUVS; mesophotic habitats; rhodolith beds; south-western Atlantic Ocean